2015
DOI: 10.3389/fmicb.2015.01151
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic insights into the intricate gut microbial–host interaction in the development of obesity and type 2 diabetes

Abstract: Gut microbiota has recently been proposed as a crucial environmental factor in the development of metabolic diseases such as obesity and type 2 diabetes, mainly due to its contribution in the modulation of several processes including host energy metabolism, gut epithelial permeability, gut peptide hormone secretion, and host inflammatory state. Since the symbiotic interaction between the gut microbiota and the host is essentially reflected in specific metabolic signatures, much expectation is placed on the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 87 publications
3
78
1
1
Order By: Relevance
“…Since the xeno‐metabolome is strongly influenced by the intricate relationship between the host metabolism, the diet, and the gut microbiota composition and activity , starvation, alterations in vitamin status (i.e., biotin, niacin), and changes in the gut microflora following both types of procedures for weight are all possibly implicated. The gut microbiota have been particularly associated with the development of obesity and its comorbidities, mainly due to their contribution in the modulation of several processes including host energy metabolism, gut epithelial permeability, gut peptide hormone secretion, and host inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the xeno‐metabolome is strongly influenced by the intricate relationship between the host metabolism, the diet, and the gut microbiota composition and activity , starvation, alterations in vitamin status (i.e., biotin, niacin), and changes in the gut microflora following both types of procedures for weight are all possibly implicated. The gut microbiota have been particularly associated with the development of obesity and its comorbidities, mainly due to their contribution in the modulation of several processes including host energy metabolism, gut epithelial permeability, gut peptide hormone secretion, and host inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, metabolomics—namely the comprehensive study of ideally all endogenous and exogenous metabolites contained in a biological system at a given moment—is currently considered as the most appropriate omics technology to investigate complex, polygenic, and multifactorial diseases with a strong multisystemic metabolic nature such as obesity and T2D .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, numerous studies have concluded that the gut microbiota is linked with host obesity and energy metabolism167, potentially via the connection between the gut microbes and body fat absorption and disposition89. For instance, the phylum, Firmicutes , is more abundant in obese than lean individuals, and vice versa for Bacteroidetes .…”
mentioning
confidence: 99%
“…53 Moreover, colonic bacteria are responsible for metabolizing bile acids. 54 The homeostasis of all these metabolic processes helps the host be healthy. Thus, alterations in the co-metabolism of bile acids, branched fatty acids, choline, purine, vitamins, and phenolic compounds have been associated with the development of metabolic diseases such as obesity and type 2 diabetes.…”
Section: Role Of the Gut Microbiome In Healthmentioning
confidence: 99%